The e-monetary theory - Duong Ngotran (Economics: The Open-Access, Open-Assessment E-Journal, 2020)
The author develops a dynamic model with two types of electronic money: reserves for transactions between bankers and zero-maturity deposits for transactions in the non-bank private sector. Using this model, he assesses the efficacy of unconventional monetary policy since the Great Recession. After quantitative easing, keeping the interest on reserves near zero too long might create deflation. The central bank can safely get out of the "low rate-cum-deflation' trap by 'raising rate and raising money supply".
http://dx.doi.org/10.7910/DVN/NOSVZE
Keywords: E4; E5; 330; Interest on reserves; quantitative easing; unwinding QE; e-money; excess reserves; raise rate raise money supply